Neural activity patterns in the chemosensory network encoding vomeronasal and olfactory information in mice - Pardo-Bellver, Cecília; Vila-Martin, Manuel E.; Martínez-Bellver, Sergio; Villafranca-Faus, María; Teruel-Sanchis, Anna; Savarelli-Balsamo, Camila A.; Drabik, Sylwia M.; Martínez-Ricós, Joana; Cervera-Ferri, Ana; Martínez-García, Fernando; Lanuza, Enrique; Teruel-Martí, Vicent (Frontiers in Neuroanatomy, 2022)
Rodents detect chemical information mainly through the olfactory and vomeronasal systems, which play complementary roles to orchestrate appropriate behavioral responses. To characterize the integration of chemosensory information, we have performed electrophysiological and c-Fos studies of the bulbo-amygdalar network in freely behaving female mice exploring neutral or conspecific stimuli. We hypothesize that processing conspecifics stimuli requires both chemosensory systems, and thus our results will show shared patterns of activity in olfactory and vomeronasal structures. Were the hypothesis not true, the activity of the vomeronasal structures would be independent from that of the main olfactory system. The population activity elicited by olfactory and vomeronasal stimuli was recorded in the main and accessory olfactory bulbs, the medial amygdala (which receives both olfactory and vomeronasal inputs) and the posteromedial cortical amygdala (a strictly vomeronasal structure). The neuronal activity of these areas was segmented in behaviorally relevant epochs, and Granger’s causality was applied to investigate the transfer of information between them. Chemosensory exploration elicited significant interactions among these structures, characterized by alternating periods of strong and weak amygdala dominance over the bulbs. The input from the bulbs appeared during periods of weak amygdaloid control. The causal analysis in the frequency domain showed that the amygdaloid control over the bulbs involved high gamma oscillations, whereas the bulbar input to the amygdala occurred in the beta and low gamma bands. These beta and gamma waves, nested to theta rhythmicity, seem to represent the nature of the stimulus on this network. In the c-Fos analysis, we assessed the activation elicited by neutral olfactory or male stimuli in a broader network. Male urine induced a significantly higher activity in the vomeronasal system compared to that induced by a neutral odorant. Concerning the olfactory system, only the cortex-amygdala transition area showed significant activation. No differential c-Fos expression was found in the reward system and the basolateral amygdala. These functional patterns in the chemosensory circuitry reveal a strong top-down control of the amygdala over both olfactory bulbs, suggesting an active role of the amygdala in the integration of chemosensory information directing the activity of the bulbs during environmental exploration.